The consequences of humiliation : anger and status in world politics - Barnhart, Joslyn (Cornell University Press, 2020)
"This book explores the nature of national humiliation and its impact on foreign policy, demonstrating that Germany's catastrophic reaction to its humiliation at the end of World War I was far from an anomaly. Instead it represents a broader pattern of international behavior in which states that have experienced humiliating events are more likely to engage in acts of international aggression aimed at restoring the state's image"--